PERAN ORANG TUA DALAM MEMBIMBING MINAT BELAJAR ALQUR’AN PADA ANAK DI DUSUN MULYOAGUNG DESA MULYOASRI KECAMATAN AMPELGADING - Widyawati Widyawati (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Education is the most important thing for all humans to determine their future. With the existence of human education, life can be a directed person. Education is not only borne by the school or the teacher, but the most important role in education is the role of parents and families. The first education is in the family or parents. This research was conducted in Mulyoasri Village, Ampelgading District. Data collection is done by the method of observation of researchers on the phenomena that occur in the field, also carried out by the method of interviewing researchers with data sources, also carried out the method of documentation in the form of notes or archives. The interest in learning al-quran in children is included in the medium category. Which is meant is that there are some children who are enthusiastic in learning al-quran, some are less enthusiastic. The spirit that exists in children is inseparable from the role of parents as educators, as protectors, motivators, facilitators, and as mentors. But in the role of parents, there are still factors that influence it, starting from the fact that is in the child, namely there is a sense of laziness, children's intelligence, and shame. factors that are outside the information technology child, television, parental support, and the atmosphere of the house that does not support. Keywords: the role of parents, guiding interest in learning the children of the qur'a